Anaerobic degradation of 2-fluorobenzoate by benzoate-degrading, denitrifying bacteria. - Schennen, U (1985)
Three strains of anaerobically benzoate-degrading, denitrifying bacteria of the genus Pseudomonas were able to grow on 2-fluorobenzoate as the sole carbon and energy source. Fluoride ion release was stoichiometric, and the reduction of dissolved organic carbon indicated total degradation. Cells grown anaerobically with benzoate were adapted for immediate growth with 2-fluorobenzoate, and both compounds were substrates for an inducible benzoyl-coenzyme A synthetase, the initial enzyme of anaerobic degradation. It is proposed that fluoride is eliminated gratuitously by a regioselective reaction in a sequence common to both carbon sources. Benzoate, but not 2-fluorobenzoate, was oxidized by aerobically grown cells.